Trends and hotspots of stereoelectroencephalogram from 2002 to 2023: a bibliometric analysis - Wang, Tianren; Dong, Hengxin; Li, Kaiwei; Feng, Tao; Yang, Yanfeng; Chen, Sichang; Lu, Di; Wei, Penghu; Shan, Yongzhi; Zhao, Guoguang (Frontiers in Neurology, 2024)
BackgroundStereoelectroencephalography (SEEG), as a minimally invasive method that can stably collect intracranial electroencephalographic information over long periods, has increasingly been applied in the diagnosis and treatment of intractable epilepsy in recent years. Over the past 20 years, with the advancement of materials science and computer science, the application scenarios of SEEG have greatly expanded. Bibliometrics, as a method of scientifically analyzing published literature, can summarize the evolutionary process in the SEEG field and offer insights into its future development prospects.MethodsThis article selected all the literature records retrieved on November 4, 2024, from the Web of Science Core Collection (WoSCC). The search terms were as follows: “Stereo-electroencephalography” or “Stereo electroencephalography” or “Stereo-EEG” or “Stereo EEG” or “SEEG.” The document types included were research articles and reviews. For analysis, VOSviewer, CiteSpace, and the R package “bibliometrix” were employed to analyze various aspects of the SEEG field, including authors, institutions, countries and regions, and research hotspots.ResultsWe reviewed a total of 1,383 non-duplicate literature records from 2002 to 2023, including 1,241 research articles, 116 review articles and 26 letters. Observing the annual publication trends, there has been an overall increase since 2002. The most influential journal in this field is Epilepsia. Other journals with considerable impact include Clinical Neurophysiology, Epileptic Disorders, Epilepsy Research, NeuroImage, and Epilepsy & Behavior. The top 5 most influential scholars are Bartolomei F, Tassi L, Nobili L, Russo GL, and Mc Gonigal A. As for the analysis of countries and regions, France occupies a leading position in this field with its early start, while China and the United States have also emerged as focal points since 2020. Research on SEEG has expanded beyond its initial use for localizing epileptic foci and thermo-coagulation treatments and have been employed as a medium to facilitate real-time prediction of epileptic seizures and enabling the exploration of brain network connectivity.ConclusionAs a minimally invasive tool for collecting intracranial electroencephalographic signals, SEEG continues to offer vast potential for development and application. Advances in electrode materials and robotic-assisted stereotactic techniques, have enabled SEEG to simultaneously sample multiple brain regions, acquire electrical signals from deep brain structures. These advantages significantly enhance the precision of epileptic focus localization in diagnosis and treatment, addressing the limitations of subdural electrodes. Through bibliometric analysis, this paper traces the developmental trajectory of SEEG and identifying key technological milestones, thereby providing a reference for scholarly research directions.